2014
DOI: 10.1038/ijo.2014.198
|View full text |Cite
|
Sign up to set email alerts
|

Blocking CD40-TRAF6 interactions by small-molecule inhibitor 6860766 ameliorates the complications of diet-induced obesity in mice

Abstract: Our results indicate that small-molecule-mediated inhibition of the CD40-TRAF6 interaction is a promising therapeutic strategy for the treatment of metabolic complications of obesity by improving glucose tolerance, by reducing the accumulation of immune cells to the adipose tissue and by skewing of the immune response towards a more anti-inflammatory profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 33 publications
2
33
1
Order By: Relevance
“…Nonetheless, we observed that these differences are specific to adipose tissue, which is in line with the unique nature of adipose tissue T regs and their unique functional capacity compared with other induced T reg populations (e.g., spleen) [48,49]. metabolism [17,19]. Certainly, CD40 expression on nonhematopoietic cells is an important contributor.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Nonetheless, we observed that these differences are specific to adipose tissue, which is in line with the unique nature of adipose tissue T regs and their unique functional capacity compared with other induced T reg populations (e.g., spleen) [48,49]. metabolism [17,19]. Certainly, CD40 expression on nonhematopoietic cells is an important contributor.…”
Section: Discussionsupporting
confidence: 54%
“…CD40 deficiency in T cells potentiated adipose tissue inflammation during obesity, suggesting a protective function for CD40 signaling [29,30]. By contrast, a chemical blockade of CD40-TRAF6 signaling, but not signaling through TRAF2/3/5, protected mice from obesity-induced insulin resistance and hepatosteatosis [17,19]. Obviously, variable results in these studies may be attributed to differences in the diet used to induce obesity, to environmental conditions, to differences in gut microbiota, or to the genetic background strains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7C). Additional pathways linked to diabetic complications, including TRAF6, complement, platelet activation and RAGE receptor 3538 were also enriched, albeit to a lesser extent. Regardless of magnitude, the combined effects of the complication pathways activated in TBDM and linked to TB susceptibility suggest bidirectional pathological interactions between TB and DM.
Figure 7Increased activity of pathways associated with epigenetic regulation in diabetic TB patients.
…”
Section: Resultsmentioning
confidence: 99%
“…Obesity and related complications are controlled by interconnected protein networks, which can be targeted for obesity management [2]. Recently, numerous researchers have reported important target proteins along with their inhibitors as anti-obesity drugs to combat obesity and related complications [3,4]. Nonetheless, proper obesity management still needs novel anti-obesity drugs that target obesity-associated molecules.…”
Section: Introductionmentioning
confidence: 98%